Psiko Edukasi Kesehatan Mental pada Siswa Kelas IX di SMP Negeri 20 Surakarta - Viona Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
In initial observations at SMP Negeri 20 Surakarta, various emotional and behavioral problems were found among students, including self-injurious behavior due to emotional stress, such as friendship conflicts and social pressure. This phenomenon highlights the importance of psychosocial interventions to increase awareness of mental health among adolescents. Adolescence, as a critical period of biological, psychological and social development, is vulnerable to internal and external conflicts that can affect mental well-being. Data shows that the prevalence of emotional mental disorders in adolescents is increasing, with risk factors including academic pressure, poor interpersonal relationships, and lack of mental health awareness and support. To overcome this, community service activities in the form of mental health psychoeducation were carried out at SMP Negeri 20 Surakarta. This activity includes training in managing emotions, strengthening interpersonal relationships, and increasing student awareness about the importance of mental health. Results show increased student understanding and awareness, as well as positive impacts on psychological well-being, social skills, and academic achievement. It is hoped that this program will be the first step in supporting adolescent mental health and reducing the risk of psychological disorders in the future.